PRODUKTIVITAS PRIMER DAN FAKTOR FISIKA-KIMIA DI PERAIRAN TELUK AMBON DALAM - Iskandar A.H Pelupessy; N V Hulliselan; Irma Kesaulya; Malik S Abdul (Prosiding Seminar Nasional Kemaritiman dan Sumber Daya Pulau-Pulau Kecil, 2017)
Primary productivity level in a certain water body, generally related to the abundance of resources on that water area. Primary productivity as the photosynthesis rate can be stated as the amount of carbon (gram) produced in one square meter of water column in a day. Geomorphologically, inner Ambon bay has various functions such as; fishery resources for local inhabitant especially lure fisheries and mariculture area, furthermore the shore land is becoming residential areas. Inner Ambon bay is a good healthy water mass, however the increase number of population and development activities around the bay give negative impacts to the inner Ambon bay. The waste comes from household, agriculture, fishery, industry and transportation that flow through the rivers and disembogue at the inner Ambon bay. From the parameters observed in this research, Ambon Bay is indicated facing the water fertility degradation. The experiment was conducted in March and april 2015.Keywords : primary productivity, carbon, physical, chemical